Sperm count of Macrobrachium amazonicum (Heller, 1862) populations with distinct life histories, with introduction of a simple counting method - Paschoal, Lucas Rezende Penido [UNESP]; Zara, Fernando José [UNESP] (Elsevier, 2018)
Sperm count is an important quality assessment tool in farming programs and stock improvement in crustaceans. However, this procedure is still little used in caridean shrimps and standardization of appropriate techniques for the group is lacking. In this study, we propose a simple protocol adapted to determine sperm count in carideans using as model the Amazon River prawn Macrobrachium amazonicum. Males of dominant morphotypes (GC1 and GC2) of this species with amphidromous and hololimnetic life cycles were collected and carefully dissected. The ejaculatory duct was removed from the vas deferens and dissociated in a solution of distilled water (9 μl) and methylene blue (1 μl). Subsequently, 1 μl of this new solution was added to distilled water (9 μl), and then 1 μl was pipetted and quantified in a Neubauer chamber. The feasibility of this technique was also evaluated in animals preserved (5–480 days) in 70% ethanol from collections and the structural morphology of spermatozoa (spz) was examined. Despite morphometric differences observed between different types of males, the mean sperm count was similar for the species. In amphidromous animals, 60,258 spz/μl were registered for GC1 and 65,308 spz/μl for GC2, while in hololimnetic prawns, 48,950 spz/μl were registered in GC1 and 53,850 spz/μl in GC2. The variation in sperm count among animals preserved for different periods of time was small and very similar to those of fresh animals. Also, no microscopic changes in the structures of spz were observed. This technique can be applied to obtain a spermiogram in fresh as well as preserved animals, being especially important in studies with animals examined in population studies and deposited in collections or laboratories. This protocol can be used as a general model for spermiogram in caridean shrimps due to the great similarity of male reproductive systems within the group.
Keywords: Animals preserved in ethanol; Caridea; Morphotypes; Sperm count; Spermatozoa